2021
DOI: 10.1002/eji.202149488
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD137 is a novel serum marker of liver cirrhosis in patients with hepatitis C and alcohol‐associated disease etiology

Abstract: Defective T-cell functions play a role in the persistence of HCV infection. Activated T cells express CD137, which costimulates antivirus T-cell responses, and this activity is antagonized by soluble CD137 (sCD137). Here, we show that in sera of 81 patients with chronic HCV, sCD137 levels did not correlate with measures of viral infection, and did not decline after virus eradication using direct-acting antivirals. Thus, serum sCD137 was similar in patients infected with HCV and in uninfected controls. Of note,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Previous studies indicated higher serum sCD137 levels in patients with liver cirrhosis [18]. The plasma sCD137 levels of the 30 SIRS/sepsis patients with liver cirrhosis tended to be elevated, though not significantly (p = 0.053; Figure 1b).…”
Section: Plasma Scd137 Levels Of the Sirs/sepsis Patients In Relation...mentioning
confidence: 67%
See 3 more Smart Citations
“…Previous studies indicated higher serum sCD137 levels in patients with liver cirrhosis [18]. The plasma sCD137 levels of the 30 SIRS/sepsis patients with liver cirrhosis tended to be elevated, though not significantly (p = 0.053; Figure 1b).…”
Section: Plasma Scd137 Levels Of the Sirs/sepsis Patients In Relation...mentioning
confidence: 67%
“…The serum concentrations of sCD137 of patients with acute pancreatitis were also elevated in contrast to healthy controls, and were related to disease severity and mortality [24]. The higher sCD137 of patients with HCV-related liver cirrhosis correlated with serum tumor necrosis factor levels [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 34 Moreover, a high level of sCD137 was detected in the serum of HCV and alcohol-associated cirrhosis patients, suggesting that sCD137 does play a role in liver pathologies. 19 …”
Section: Discussionmentioning
confidence: 99%